(untitled) (Global Journal of Computer Science and Technology, 2012)
The e-Governance (digital government or online government) refers to government2019;s use of information technology to exchange information and services with citizens, businesses, and other arms of government. E-Governance is a process of reform in the way Governments work, share information, engage citizens and deliver services to external and internal clients for the benefit of both government and the clients that they serve. This paper studies the current status of e-governance and future of e-governance in Punjab.